THE ROLE OF TRAINING AND DEVELOPMENT IN THE PROCESS OF IMPROVING EMPLOYEE ACHIEVEMENT - Garaika Garaika (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2019)
Training activities cannot be ignored, especially in entering the era of increasingly fierce, sharp, intense competition in this millennium century. In this connection we realize that training is fundamental for employees. By following the development and growth, which is marked by the greater diversification of the workforce, the form of organization and global competition that continues to increase, training and development efforts enable employees to expand their obligations and greater responsibilities. The effectiveness of training and development depends on the integrity of the employees with other HR activities. Providing incentive compensation such as stock options and additional benefits, such as an attractive retirement plan, is a temporary effective way to reduce turnover, especially among executives.